Multiple analyses in clinical trials - Moye, Lemuel (Henry Stewart Talks, 2007)
Definition of a clinical trial, The great compromise of medical research, The populations can fool us, Extending to the population, Appropriate sampling, Trustworthy estimates, Random research, Experimental corruption, Prospectively designed research, Patience and tight protocols, Endpoints, Community responsibility, Investigator mandate, P-values: pros and cons, Evolution in trial methodology, Argument for multiple endpoints, Conflict within trial interpretation, Type I error inflation, Bonferroni correction, Negative primary endpoints
Archived at 2018/05/31